Riksmaten 1997-98 - National Food Agency (National Food Agency, 2021)
In 1997-98, the Statistics Sweden in co-operation with the National Food Administration (NFA) carried out the second nationwide Swedish dietary survey, Riksmaten. The study was a follow-up of the previous survey (Hulk) carried out in 1989, using similar design and methods. In Riksmaten a representative sample of 2000 households consisted the survey base. In each household one person, aged 18-74 years, was selected to register food intake in a precoded 7-days record book. The participants also filled in a questionnaire with information on body weight, height, education, occupation, physical activity, smoking habits and other lifestyle factors. The sampling design was continuous, i.e. a number of households were invited to participate every second week, thus covering the whole year.

The population in Riksmaten 1997-98 was all registered persons in Sweden between 18-74 years. Subjects were drawn by using systematic sampling from a population register. The selection was based on 2,027 individuals and participation rate comprised 60 %.

The survey contained 32 questions (regarding height, weight, use of supplements, the type of fats and salt in cooking, smoking and snuff, exercise , education , health status etc.).

Purpose:

The aim was to examine food consumption and nutrient intake among women and men in Sweden.

The dataset contains food registry and a survey from the study participants.

Riksmaten 1997-98 är den andra rikstäckande kostundersökningen, baserad på ett representativt urval, som genomförts. Den första, ”Hushållens livsmedelsutgifter och kostvanor” (Hulk), genomfördes 1989 av Statistiska centralbyrån (SCB) tillsammans med Livsmedelsverket. I båda dessa undersökningar har dels de deltagande hushållen bokfört samtliga inköp av livsmedel under en fyra veckors period, dels en person i hushållet registrerat matintaget under en vecka med hjälp av en så kallad menybok samt även besvarat ett antal frågor.

Undersökningspopulationen i Riksmaten 1997-98 var alla folkbokförda personer i Sverige mellan 18−74 år. Personerna drogs med med hjälp av systematiskt urval från ett register över totalbefolkningen, RTB-S. Urvalet baserades på 2027 personer och deltagarfrekvensen omfattade 60 %.

Menyboken som användes för registrering av matintag bestod av förtryckta alternativ för maträtter och livsmedel. I menyboken skulle även plats och tidpunkt för måltiden registreras. Mängdangivelsen av livsmedel gavs i hushållsmått eller som portionsstorlek. För vissa huvudkomponenter samt matfett fanns möjlighet att skatta portionsstorleken med hjälp av bilder, där fyra alternativ gavs. Portionsstorlekarna byggde på resultat från tidigare undersökningar samt på uppgifter från Livsmedelsverkets vikttabeller.

Frågeformuläret innehöll totalt 32 frågor (avseende exempelvis längd, vikt, typ av kost, användning av kosttillskott, typ av matfett och salt i matlagning, rökning och snusning, motion, utbildning och hälsotillstånd).

Syfte:

Studiens syfte var att undersöka livsmedelskonsumtion och näringsintag bland kvinnor och män i Sverige.

Dataset innefattar kostregistrering och enkät från studiens deltagare.
Riksmaten 1997-98
Keywords: Adult; Vuxna; Diet Surveys; Kostundersökningar; Socioeconomic Factors; Socioekonomiska faktorer; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Lipids; Fetter; Coffee; Kaffe; Cholesterol; Kolesterol; Tobacco, Smokeless; Rökfri tobak; Vitamins; Vitaminer; FOOD; LIVSMEDEL; Nutrition Policy; Näringsrekommendationer; Recommended Dietary Allowances; Rekommenderat kostintag; Proteins; Proteiner; Energy Intake; Energiintag; Diet Records; Kostregistrering; Carbohydrates; Kolhydrater; Alcoholic Beverages; Alkoholhaltiga drycker; Candy; Godis; Carbonated Beverages; Kolsyrade drycker; Dairy Products; Mejeriprodukter; Dietary Fiber; Kostfibrer; Disaccharides; Disackarider; Eggs; Ägg; Fatty Acids; Fettsyror; Fatty Acids, Monounsaturated; Fettsyror, enkelomättade; Feeding Behavior; Ätbeteende; Food; Livsmedel; Ice Cream; Glass; Meat; Kött; Meat-Packing Industry; Kött- och charkuteriindustri; Minerals; Mineral; Nuts; Nötter; Sucrose; Sackaros; Tea; Te; Vegetables; Grönsaker; Fatty Acids, Omega-3; Omega-3-fettsyror; Seafood; Fisk och skaldjur; Dietary Sucrose; Strösocker; Fatty Acids, Omega-6; Omega-6-fettsyror; Trans Fatty Acids; Transfetter; Fast Foods; Snabbmat; Drinking Water; Dricksvatten; Tobacco Use; Tobaksanvändning; DIET AND EXERCISE; MOTION OCH MATVANOR; minerals; mineralämnen; nutrition; nutrition; food groups; livsmedelsgrupper; dietary guidelines; kostråd; food consumption; livsmedelskonsumtion